Shadow's bane - Chance, Karen (Chance, Karen. Midnight's daughter novels., 2018)
Dorina Basarab is a dhampir--half-human, half-vampire. As one of the Vampire Senate's newest members, Dory already has a lot on her plate. But then a relative of one of Dory's fey friends goes missing. They fear he's been sold to a slaver who arranges fights--sometimes to the death--between different types of fey. As Dory investigates, she and her friends learn the slavers are into something much bigger than a fight club. With the Vampire Senate gearing up for war with Faerie, it'll take everything she has to defeat the slavers--and deal with the entirely too attractive master vampire Louis-Cesare....